Fatores de risco para injúria renal aguda em pacientes submetidos à hepatectomia parcial - Bredt, Luis César (2017)
This research aims to identify risk factors for the occurrence of acute kidney injury (AKI) in the postoperative period of partial hepatectomies. Methods: Retrospective analysis of 446 consecutive resections in 405 patients, analyzing clinical characteristics, preoperative laboratory data, intraoperative data, and postoperative laboratory data and clinical evolution. Adopting the International Club of Ascites (ICA) criteria for the definition of AKI, potential predictors of AKI by logistic regression were identified. Results: Of the total 446 partial liver resections, postoperative AKI occurred in 80 cases (17.9%). Identified predictors of AKI were: non-dialytic chronic kidney injury (CKI), biliary obstruction, the Model for End-Stage Liver Disease (MELD) score, the extent of hepatic resection, the occurrence of intraoperative hemodynamic instability, post-hepatectomy haemorrhage (PHH), and postoperative sepsis. Conclusion: The MELD score, the presence of non-dialytic CKI and biliary obstruction in the preoperative period, and perioperative hemodynamics instability, bleeding, and sepsis are risk factors for the occurrence of AKI in patients that underwent partial hepatectomy.